Union Pacific the reconfiguration : America's greatest railroad from 1969 to the present - Klein, Maury 1939- (New York Oxford Oxford University Press, 2011)
Volumes I and II of this history of the Union Pacific Railroad covered the years 1863-1969. This volume brings the story of the Union Pacific - the oldest, largest, and most successful railroad of modern times - fully up to date. The book follows the trajectory of an icon of the industrial age trying to negotiate its way in a post-railway world, plagued by setbacks such as labour disputes, aging infrastructure, government de-regulation, ill-fated mergers, and more.
Includes bibliographical references and index.
Keywords: Union Pacific Railroad Company -- History; Electronic books; Railroads -- United States -- History